Crime and Violence in Central America : A Development Challenge - Executive Summary - World Bank (World Bank, 2012)
Crime and violence are now a key development issue for Central American countries. In three nations El Salvador, Guatemala, and Honduras crime rates are among the top five in Latin America. This report argues that successful strategies require actions along multiple fronts, combining prevention and criminal justice reform, together with regional approaches in the areas of drug trafficking and firearms. It also argues that interventions should be evidence based, starting with a clear understanding of the risk factors involved and ending with a careful evaluation of how any planned action might affect future options. In addition, the design of national crime reduction plans and the establishment of national cross-sectoral crime commissions are important steps to coordinate the actions of different government branches, ease cross-sectoral collaboration and prioritize resource allocation. Of equal importance is the fact that national plans offer a vehicle for the involvement of civil society organizations, in which much of the expertise in violence prevention and rehabilitation resides. Prevention efforts need to be complemented by effective law enforcement. The required reforms are no longer primarily legislative in nature because all six countries have advanced toward more transparent adversarial criminal procedures. The second-generation reforms should instead help deliver on the promises of previous reforms by: (i) strengthening key institutions and improving the quality and timeliness of the services they provide to citizens; (ii) improving efficiency and effectiveness while respecting due process and human rights; (iii) ensuring accountability and addressing corruption; (iv) increasing inter-agency collaboration; and (v) improving access to justice, especially for poor and disenfranchised groups. Specific interventions reviewed in the report include: information systems and performance indicators as a prerequisite to improve inter-institutional coordination and information sharing mechanisms; an internal overhaul of court administration and case management to create rapid reaction, one-stop shops; the strengthening of entities that provide legal counseling to the poor and to women; and the promotion of alternative dispute-resolution mechanisms and the implementation of community policing programs.